Achilles Tendon Repair With the PARS: Innovative Double Locking Techniques and Device Positioning Based on MRI Study. Issue 4 (December 2017) - MacMahon, Aoife; Jones, Mackenzie T.; Deland, Jonathan T.
Abstract : A variety of surgical techniques for Achilles tendon rupture repair have been reported, including open, percutaneous, and limited-open approaches. One device which has recently become available is the Percutaneous Achilles Repair System (PARS), which uses both locking and nonlocking sutures for Achilles tendon rupture repair. This article presents techniques using double locking or 2 locked repair sutures in each tendon, along with the standard repair technique. An important component of these techniques is anatomic positioning of the PARS, keeping the arms parallel to the Achilles tendon and properly externally rotated using the results of a magnetic resonance imaging study to improve tendon capture. Early studies have shown good clinical outcomes and suggest that minimally invasive techniques such as the PARS are clinically and biomechanically suitable alternatives to open repair for Achilles tendon ruptures. Level of Evidence: Diagnostic Level V, expert opinion. See Instructions for Authors for a complete description of levels of evidence.